Efficacy of levofloxacin as an antibacterial prophylaxis for acute leukemia patients receiving intensive chemotherapy: a systematic review and meta-analysis - Owattanapanich, Weerapat; Chayakulkeeree, Methee (Hematology (Luxembourg), 2019)
The incidence of febrile neutropenia (FN) in acute leukemia patients following induction or consolidation chemotherapy is high. Several clinical practice guidelines recommend the use of a fluoroquinolone prophylaxis to prevent bacterial infection in patients being prone to prolonged profound neutropenia. This systematic review and meta-analysis aimed to investigate the efficacy and complications of levofloxacin as a prophylaxis for FN patients following chemotherapy for acute leukemia. Two databases from MEDLINE and EMBASE were searched for published studies indexed before 10 July 2018. A total of 862 acute leukemia patients were included, with 356 in the levofloxacin prophylaxis arm and 506 in the no-prophylaxis arm. Patients receiving levofloxacin had a significantly lower FN rate than patients who did not receive the antibiotic prophylaxis (odds ratio [OR]: 0.43, 95% confidence interval [CI]: 0.32-0.58, p < .00001, I 2 = 0%). The rate of microbiologically documented infection in the no-prophylaxis group was higher than that for the levofloxacin prophylaxis group (OR: 0.45, 95% CI: 0.34-0.60, p < .00001, I 2 = 0%). The bacteremia rate in the levofloxacin prophylaxis group was significantly lower than that for the no-prophylaxis group (OR: 0.45, 95% CI: 0.31-0.66, p < .00001, I 2 = 0%). However, the mortality rates of the two groups were quite similar between the two groups (OR: 0.67, 95% CI: 0.34-1.33, p = .26, I 2 = 0%). Although the levofloxacin prophylaxis for the acute leukemia patients receiving intensive chemotherapy showed advantages for infectious complications, it did not affect mortality.